Analisis Perbandingan Miskonsepsi Siswa Kelas VI pada Materi Teorema Pythagoras di SDN 5 Menteng dan SDN 8 Menteng - Septiani Anggraini; Anisa Astia; Rizal Basri (CV. ITTC INDONESIA, 2026)
This study aims to analyze and compare the misconceptions of sixth-grade students on the Pythagorean Theorem material at SDN 5 Menteng and SDN 8 Menteng using a reasoned questionnaire. This study employed a descriptive quantitative approach supported by simple qualitative analysis of students’ reasons for their answers. The research subjects consisted of 30 students, with 15 students from each school. The research instrument was a reasoned questionnaire containing four statements related to the basic concepts and application of the Pythagorean Theorem. Quantitative data were analyzed using percentages, while qualitative data were analyzed by grouping students’ reasons into categories of understanding the concept, lack of conceptual understanding, and misconceptions. The results showed that most students had understood the basic concepts of the Pythagorean Theorem, especially the concept of right triangles. However, misconceptions were still found in the use of formulas to determine unknown sides and in recognizing certain right triangle patterns. Students of SDN 8 Menteng demonstrated a better level of understanding than students of SDN 5 Menteng. Therefore, more contextual, visual, and varied learning approaches are needed to help students understand the application of the Pythagorean Theorem comprehensively.